Coping Stress Recovery Agent in Community-Based Intervention Programs (IBM) - Santi Fatmawati; Siti Fitriana; Suhendri (Universitas PGRI Yogyakarta, 2026)
The rising prevalence of drug abuse in Indonesia has prompted the National Narcotics Agency to implement Community-Based Intervention (IBM) programs, positioning recovery agents as frontline providers of psychosocial support. These agents face significant work-related stress from client mentoring, administrative duties, and community stigma, yet research on their coping experiences remains scarce. This study aims to explore the coping strategies used by recovery agents in the IBM Program in Gayamsari Subdistrict, Semarang City, Indonesia. A qualitative phenomenological approach was employed, involving three recovery agents purposively selected based on preliminary questionnaire results that represented high, moderate, and low work-stress levels. Data were collected through semi-structured interviews and non-participant observation and analyzed using thematic analysis with NVivo 15 software. The findings reveal that recovery agents employ dynamic combinations of problem-focused coping (confrontative coping, planful problem solving, and seeking social support) and emotion-focused coping (distancing, self-control, positive reappraisal, accepting responsibility, and escape-avoidance). Comparative analysis indicates that coping effectiveness correlates with emotional regulation maturity, as lower-stress agents demonstrate more integrated coping repertoires. Institutional support from the National Narcotics Agency and community acceptance significantly influence the effectiveness of coping. This study addresses a critical research gap regarding the subjective coping experiences of recovery agents in community-based rehabilitation. The findings highlight the importance of structured psychosocial support, regular supervision, peer support groups, and culturally adapted stress management training to enhance agent well-being and program sustainability. Keywords: community-based intervention, Indonesia, phenomenology, recovery agents, stress coping